Інформаційна технологія попередньої обробки зображень для виявлення прихованих мін з використанням осциляторної згорткової нейронної мережі Хопфа - Панас, Іван Андрійович; Panas, Ivan Andriiovych (Національний університет "Львівська політехніка", 2024)
Проблема прихованих мін залишається однією з найгостріших у країнах, що зазнали військових дій. На сьогодні потреба у надійних, точних і автоматизованих методах виявлення мін є надзвичайно високою, особливо в контексті гуманітарного розмінування в Україні. Георадарні системи (Ground Penetrating Radar, GPR), що використовують B-скан-зображення, дають змогу отримати інформацію про підповерхневу структуру ґрунту. Однак ці дані потребують складної попередньої обробки через високий рівень шумів, змінну якість сигналів та неоднорідність середовища. Об'єкт дослідження - процес обробки георадарних зображень. Предмет дослідження - методи виявлення гіперболічних ознак, що відповідають підозрілим об’єктам (мінам), у B-сканах. Метою дослідження є розробка інформаційної технології автоматизованої попередньої обробки георадарних зображень із використанням осциляторної згорткової нейронної мережі Хопфа (OCNN-Hopf), що забезпечує високу точність класифікації, швидкість і стабільність в умовах польового використання. Наукова новизна полягає у впровадженні згорткової мережі з HopfConv-шаром, що моделює просторово-часові ознаки B-сканів. Уперше реалізовано інтеграцію цієї архітектури з аугментацією, формуванням патчів та глибоким навчанням, що забезпечило високу точність при мінімальних помилках. Розроблений програмний модуль охоплює всі етапи обробки, тренування та оцінки, має систему конфігурації та логування. Метод AHP використано для обґрунтування архітектурного вибору. Рішення готове до польового застосування й подальшого розвитку.

The problem of hidden landmines remains a serious threat in post-conflict zones worldwide. In particular, Ukraine requires reliable, fast, and accurate automated mine detection tools for humanitarian demining. Ground Penetrating Radar (GPR) systems provide subsurface imaging in the form of B-scans but are often hindered by significant signal noise, soil heterogeneity, and variable environmental conditions. To address these challenges, this work proposes an innovative preprocessing pipeline combined with a Hopf-based convolutional neural network. Study object - preprocessing of ground-penetrating radar (GPR) images. Scope of research - automated detection of hyperbolic patterns corresponding to potential mines. Goal of research - to develop an information technology for detecting mines in B-scans using an Oscillatory Convolutional Hopf Neural Network (OCNN-Hopf), ensuring high detection accuracy and robustness in real-time field applications. The scientific contribution includes a novel integration of the HopfConv layer, which simulates phase-amplitude dynamics to capture spatiotemporal features. Combined with a custom data augmentation strategy, patch segmentation, and deep learning classification, the system demonstrated excellent results. Training with the Adam optimizer and early stopping ensured model generalization and low false negative rates. The final model achieved a great accuracy, with a negligible false negative rate. The practical implementation features modular code for preprocessing, augmentation, model training, inference, and evaluation, as well as a configuration-based parameter management system. Additionally, the Analytic Hierarchy Process (AHP) was used to justify model selection based on criteria such as compatibility, accuracy, speed, and safety. Among several candidate paradigms, the information-management system was selected as optimal. The solution is suitable for integration into demining systems, offering real-time processing, portability, and robustness. Future research may explore transformer-based architectures, model deployment to edge devices (FPGA, mobile GPU), and the collection of field GPR data under diverse soil conditions.
Image Preprocessing Information Technology for Hidden Mine Detection Using Hopf Oscillatory Convolutional Neural Network
Keywords: 6.126.00.01; георадар; B-скан; OCNN-Hopf; HopfConv; аугментація; аналіз ієрархій; виявлення мін; глибоке навчання; GPR; B-scan; OCNN-Hopf; HopfConv; data augmentation; AHP; mine detection; deep learning